HARGA SAHAM DILIHAT DARI GOOD CORPORATE GOVERNANCE DAN PROFITABILITAS PADA PERUSAHAAN PROPERTI - Atika Ivonella S; Muhammad Rivandi (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
Stock price is a factor that is very useful for a company and that must be considered by an investor. Stock prices can appear from the level of supply and demand for a stock. This study aims to determine and analyze the effect of Good Corporate Governance and Profitability variables on stock prices and to determine the relationship between variables that influence property company stock prices. The data processed is secondary data from the annual reports of 10 property companies listed on the Indonesia Stock Exchange for 2019-2021 which were selected using a purposive sampling technique. The method used in this study is the panel data regression method using eviews 12. The results of this study indicate that Good Corporate Governance has no effect on stock prices and Profitability has a positive effect on stock prices.GCG, Profitability, Stock prices